STRATEGY OF 4-ALLYLPHENOL SYNTHESIS AS DRUG PRECURSORS - Alya Salsabila, Tasya
The intermediate molecule 4-allylphenol or p-allylphenol has several applications, one of which is as a precursor for the synthesis of pharmacological compounds such as betaxolol. Betaxolol is a propanolamine-derived ?-blocker compound that is relatively cardio selective. Drug compounds classified as ?-blockers have been shown in several studies to help treat people with hypertension and glaucoma. The effective way to treat glaucoma is by reducing the IOP. In this case, betaxolol acts as a ? -1 adrenergic receptor blocking agent which will selectively block one of receptors so that it will slow down the disease progression and reduce the IOP. Based on the investigation of betaxolol compound retrosynthesis, the simplest reagent for producing betaxolol compounds can be obtained, namely 4-allylphenol (p-AP), which can be synthesized from allyl phenyl ether (APE). This research aim to synthesize APE as a precursor for the synthesis of p-AP intermediate compounds and characterize it as a synthesized product using NMR spectroscopy, as well as to investigate several techniques for synthesizing p-AP intermediate compounds as precursors for the synthesis of drug compounds via Claisen-Cope rearrangement reactions. In this research, APE compound was effectively synthesized form phenol (C6H5OH) with allyl bromide (C3H5Br) and anhydrous potassium carbonate (K2CO3) in anhydrous acetone solvent through the Williamson ether reaction at 60 ?. Different treatments were used throughout the reaction, including an overnight reaction without heating for 76 hours and an overnight reaction with heating for 72 hours. Pure APE compounds were produced with a higher yield of 60,06% during an overnight reaction followed by heating, than the yield without heating, which was 23,84%. A further strategy that has been carried out in this research is transformation of APE to allylphenol via the Claisen-Cope rearrangement reaction. The reactions were carried out in static batch and flow systems. In the batch system, two distinct reaction conditions were used: heating batch and heating batch catalyzed by H-ZSM-5. The reactions under these various circumstances produced impure mixed compound products. The H-ZSM-5 catalyzed heating reaction produced more complex compounds than the heating-only reaction. In the flow system, two reaction conditions were used: heating with or without acid-base extraction, and flow through an H ZSM-5 catalyzed column. Impure mixed compound products were produced under reaction circumstances involving acid-base extraction and/or the inclusion of H-ZSM-5 catalyst. The reaction through the H-ZSM-5 acid-catalyzed column produced more selective products, including simpler new stains on the chromatogram, than the reaction using acid base extraction. According to the reaction results, the Claisen-Cope rearrangement of APE to allylphenol occurs quite selectively in the flow system through the H-ZSM-5 catalyzed column. Products obtained then analyzed using Nuclear Magnetic Resonance (NMR) Spectroscopy.